Review of LCA studies of solid waste management systems – Part II: Methodological guidance for a better practice - Laurent, Alexis; Clavreul, Julie; Bernstad, Anna; Bakas, Ioannis; Niero, Monia; Gentil, Emmanuel; Christensen, Thomas H.; Hauschild, Michael Z. (Waste management (Elmsford), 2014)
•We perform a critical review of 222 LCA studies of solid waste management systems.•We analyse the past LCA practice against the ISO standard and ILCD Handbook guidance.•Malpractices exist in many methodological aspects with large variations among studies.•Many of these aspects are important for the reliability of the results.•We provide detailed recommendations to practitioners of waste management LCAs. Life cycle assessment (LCA) is increasingly used in waste management to identify strategies that prevent or minimise negative impacts on ecosystems, human health or natural resources. However, the quality of the provided support to decision- and policy-makers is strongly dependent on a proper conduct of the LCA. How has LCA been applied until now? Are there any inconsistencies in the past practice? To answer these questions, we draw on a critical review of 222 published LCA studies of solid waste management systems. We analyse the past practice against the ISO standard requirements and the ILCD Handbook guidelines for each major step within the goal definition, scope definition, inventory analysis, impact assessment, and interpretation phases of the methodology. Results show that malpractices exist in several aspects of the LCA with large differences across studies. Examples are a frequent neglect of the goal definition, a frequent lack of transparency and precision in the definition of the scope of the study, e.g. an unclear delimitation of the system boundaries, a truncated impact coverage, difficulties in capturing influential local specificities such as representative waste compositions into the inventory, and a frequent lack of essential sensitivity and uncertainty analyses. Many of these aspects are important for the reliability of the results. For each of them, we therefore provide detailed recommendations to practitioners of waste management LCAs.